THE HISTORY OF THE JOINT STOCK COMPANY. - Walker, C. E. (The Accounting Review, 1931)
Abstract The article presents the history of the joint stock company. Though it is not possible to discover instances of the joint stock company in England before the middle of the Sixteenth century, it must at the same time be recognized that before that date there were tendencies that would make its ultimate establishment inevitable. The trade of the Italian city states was already including western Europe in its scope and Italian finance consequently exerted an important influence in England. Naturally methods and organizations employed were copied to some extent abroad. There were two main lines of development which might result in the formation of a joint stock body. These were the medieval partnership and the growth of the idea of a corporation. The canonist doctrine on the use of capital discouraged loans while it encouraged the formation of partnerships. There were the "Commenda" and "Societas," both of which were in frequent use on the continent and were forms of the medieval partnership. In the commenda the commendator provided the capital and the commendatarius managed the investment, in the societas both contributed capital. In 1284, 1206 and 1312 certain Italian societas were granted rights to trade in England.